Penerapan Art Therapy : Menggambar pada Pasien Halusinasi Pendengaran : (Studi kasus di Paviliun Cempaka RS Ernaldi Bahar Palembang) - Alda Elvariani; Aprida Manurung; Novita Anggraini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hallucinations are mental disorders that experience impaired sensory perception, the appearance of false sensations in the form of sound, touch, sight and smell. The type of hallucination that is often experienced is auditory hallucination. One of the efforts made to reduce the signs and symptoms of auditory hallucinations is by doing drawing therapy. Reseach purposes to determine nursing care by applying drawing therapy to patients with auditory hallucinations at Ernaldi Bahar Hospital, Palembang. The design used was descriptive research by describing cases of 3 patients with auditory hallucinations. Subjects were selected according to inclusion and exclusion criteria. The intervention provided was drawing therapy for 3 days in 20 minutes. After the intervention of applying drawing therapy for 3 days with 20 minutes per visit, it was found that there was a reduction in the signs and symptoms of hallucinations as indicated by the results of the observation sheet for each patient. Mrs. A originally had 16 to 8 signs of symptoms, Mrs. M originally had 11 to 4 signs of symptoms, and Mrs. It is hoped that future researchers can carry out research on the application of drawing therapy so that it is carried out more often so that the therapy is more effective in reducing signs and symptoms in patients with hallucinations and also add respondents so that the application of the therapy provided is more effective in reducing the signs and symptoms experienced by patients.